Pylypenko-Frytsak N. A. Magic fairy tale as a source of formation and concentration of universal concepts - Pylypenko-Frytsak N. A. (Philological Treatises, 2020)
In the article the author considers magic fairy tales as means of concentration of universal concepts and gives the analysis of such concepts as Good and Harm. The Article is devoted to consideration (analysis) of magic fantastic narrations as metastory – result of art reconsideration of historical customs and ceremonies, outlook and the outknowledge recreated within the limits of ideology concrete epoch (epistemology system) by complex concepts.